Role of Sleep Duration in the Association Between Socioecological Protective Factors and Health Risk Behaviors in Adolescents. Issue 2 (February 2020) - Ordway, Monica Roosa; Wang, Guanghai; Jeon, Sangchoon; Owens, Judith
Abstract: Objective: The purpose of this study was to examine the associations of sleep duration and socioecological protective factors with patterns of adolescent risk behaviors in Fairfax County, VA—one of the largest public school districts in the United States. Methods: A total of 21, 360 and 20, 330 students in 10th and 12th grades who completed the Youth Risk Behavior Survey were included in this cross-sectional analysis. Sleep duration was measured by self-report of the average number of hours of sleep on a school night. Ten socioecological protective factors included peer-individual, family, school, and community domains. Latent class analysis was used to classify 7 risk behaviors (alcohol use, cigarette use, illicit drug use, inappropriate prescription drug use, risky sexual behavior, deviant behavior, and academic failure) into 4 class memberships (low, some, moderate, and high). Multinomial regression models were adjusted for age, sex, and race. Results: Adolescents who reported sleeping the recommended 8 to 9 hours were significantly less likely to belong to the class memberships of greater risk behaviors compared with those who reported short and long sleep duration after controlling for age, sex, race, and survey year. There was a significant inverse relationship between the number of socioecological protective factors and risk behaviors for both 10th and 12th graders. Potential risks of age, sex, and race on risk behaviors were observed. No significant interaction between sleep duration and protective factors was found in either grade. Conclusion: This study highlights the significant associations between sleep duration and risk behaviors in adolescents with diverse socioecological protective factors. Prioritization of prevention-focused resources should consider sleep duration in addition to the socioecological protective factors commonly cited in the literature when addressing adolescent risk behaviors. Abstract : This article has supplementary material on the web site: www.jdbp.org.